Aktivitas Antiinflamasi Ekstrak Etanol 96% Batang Apel Beludru (Diospyros Blancoi A.Dc.) terhadap Jumlah Limfosit, Monosit, dan Neutrofil pada Tikus Putih Jantan Galur Wistar yang Diinduksi Karagenan: Antiinflammatory Activity of 96% Ethanol Extract of Apel Beludru Stems (Diospyros Blancoi A.Dc.) to the Number of Lymphocytes, Monocytes, and Neutrophils in Carrageenan-induced Wistar Rats - Rusdi, Numlil Khaira; Bariroh, Tahyatul; Isra, Rafiq Al; Rahmat, Amalia; Fujianti, Fujianti; Prastiwi, Rini; Sunaryo, Hadi; Hariyanti, Hariyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
The potential of velvet apple plants (Diospyros blancoi A. DC) is large, further research is still needed to determine the anti-inflammatory effect on velvet apple stems (Diospyros blancoi A. DC). The purpose of this study was to determine the anti-inflammatory activity of 96% ethanol extract of velvet apple stems against the reduction of lymphocytes, monocytes, and neutrophils. A total of 25 male white rats of wistar strain were divided into 5 groups, namely the negative control group, the positive control group (Na diclofenac), the group given 96% ethanol extract of velvet apple stems with several doses, namely doses of 125 mg / kg BB, 250 mg / kg BB and 500 mg / kg BB. All test animals were made air bags on days 1 and 3, then on day 6 test preparations and carrageenan induction were carried out. On the 7th day blood was taken through the retroorbital sinuses, then the calculation of lymphocytes, monocytes, neutrophils using a microscope was carried out and the data were analyzed using One-way Anova and Kruskal Wallis test. The results showed a higher percentage of negative lymphocytes, monocytes, and neutrophils compared to the treatment group. In the treatment group, the dose of 500mg/kgBB had a significant decrease in the percentage of lymphocytes, monocytes, neutrophils compared to the negative group (p<0.05) and was not significantly different from the positive control group. Ethanol extract 96% velvet apple stem dose 500 mg/kg body weight has the greatest anti-inflammatory activity against decreasing the percentage of lymphocytes, monocytes, and neutrophils. Keywords: anti-inflammatory, apel beludru, Diospyros blancoi A. DC, lymphosite, monosite, neutrophil Abstrak Potensi tanaman apel beludru (Diospyros blancoi A. DC) yang besar, sehingga perlu penelitian lebih lanjut untuk mengetahui efek antiinflamasi pada batang apel beludru (Diospyros blancoi A. DC). Tujuan penelitian ini untuk mengetahui aktivitas antiinflamasi ekstrak etanol 96% batang apel beludru terhadap penurunan limfosit, monosit, dan neutrofil. Sebanyak 25 ekor Tikus putih jantan galur wistar dibagi menjadi 5 kelompok yaitu kelompok kontrol negatif, kelompok kontrol positif (Na diklofenak), kelompok yang diberi ekstrak etanol 96% batang apel beludru dengan beberapa dosis yaitu dosis 125 mg/kgBB, 250 mg/kgBB dan 500 mg/kgBB. Semua hewan uji dibuat kantung udara pada hari ke-1 dan ke-3, lalu pada hari ke-6 dilakukan pemberian sediaan uji dan induksi karagenan. Pada hari ke-7 diambil darah melalui sinus retroorbitalis, kemudian dilakukan perhitungan sel limfosit, monosit, dan neutrofil menggunakan mikroskop. Data dianalisis menggunakan One-way Anova dan uji Kruskal Wallis. Hasil penelitian menunjukkan jumlah limfosit, monosit, dan neutrophil kelompok kontrol negatif lebih tinggi dibandingkan dengan kelompok perlakuan. Pada kelompok perlakuan, pemberian ekstrak dosis 500mg/kgBB mengalami penurunan persentase jumlah limfosit, monosit, neutrofil terbesar secara signifikan dibandingkan kelompok negatif (p<0,05) dan tidak berbeda bermakna dengan kelompok kontrol positif. Ekstrak etanol 96% batang apel beludru dosis 500 mg/kg BB memiliki aktivitas antiinflamasi terbesar terhadap penurunan persentase jumah limfosit, monosit, dan neutrophil. Kata Kunci: antiinflamasi, apel beludru (Diospyros blancoi A. DC), limfosit, monosit, neutrophil